Electrochemically Reduced Graphene Oxide Covalently Bound Sensor for Paracetamol Voltammetric Determination - Aguirre-Quintana, M; Aguirre-Quintana, M; Segura-Segura, R; Segura-Segura, R; Paz de la Vega-Quiroz, A; Paz de la Vega-Quiroz, A; Liendo-Ibarra, F; Liendo-Ibarra, F; Penagos-Llanos, J; Penagos-Llanos, J (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Designing a highly sensitive and efficient functionalized electrode for precise drug analysis remains a significant challenge. In this work, an electrochemical sensor based on a glassy carbon electrode (GCE) modified with phenyl diazonium salts (ph) and electrochemically reduced graphene oxide (ERGO), labeled GCE/ph/ERGO, was developed for the detection of paracetamol (PAR) in pharmaceutical matrices using square wave voltammetry (SWV). The modified electrode was characterized by scanning electron microscopy (SEM), electrochemical impedance spectroscopy (EIS), and cyclic voltammetry (CV). Compared to the bare GCE, the GCE/ph/ERGO sensor demonstrated significantly improved conductivity and anodic current peak for PAR over two orders of magnitude higher, indicating a substantial enhancement in electrochemical performance. Under optimized conditions, the developed sensor exhibited a low detection limit of 18.2 nM and a quantification limit of 60.6 nM. Precision studies yielded relative standard deviations (RSDs) below 8%. The sensor demonstrated excellent selectivity in the presence of common pharmaceutical excipients and high accuracy in the analysis of generic pharmaceutical formulations, with results comparable to those obtained by the HPLC technique. These findings confirm the sensor’s reliability, stability, robustness, and suitability for routine analysis of PAR in pharmaceutical samples. © 2025 by the authors.